Pengembangan dan Pendampingan Bank Sampah Liberti menjadi Usaha yang Unggul dan Berdaya Saing - Ranny Fitriana Faisal; Musbatiq Srivani; Hilma Raimona Zadry (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
This community service program encourages the Bank Sampah Liberti to become a multi-purpose and competitive organization. The program began to be implemented in 2020 and will be carried out continuously for the next three years. So that in 2024, Bank Sampah Liberti can be a pioneer to enhance skill and knowledge for community, educational organization that can play an active role in being more aware of protecting environmental health. In addition, the resulting products can also be applied by the public and others. The initial stage of activities is carried out to make a plan for activities for 2021-2023. The activity was carried out using the Forum Discussion Group method by implementing COVID protocols. The activities started by analyze weaknesses and problems and how to plan development in 2021-2023. The results of these activities showed that in 2021 activities focused on improving marketing management, granting brand patents, enriching HR skills and expertise, and improving operational management, such as layout, use of production sites, and so on. In 2022, further programs related to financial and information management. An excellent business organization is required to have clear financial reports for the continuity of its business. In 2023, there will be a product innovation development program and optimal use of technology for business development.